UNSUR-UNSUR ADIKODRATI DALAM CINDUR MATA KABA TERJEMAHAN A. DT. MADJOINDO - Sartika, Sartika; Krisna, Eva; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by adikodratiâs substance which can be found in many people story. Adikodrati (supernatural strength) is the important one of trust object in many religion all over the world and happened to all nature symptom example: (1) in human figure; (2) animal: (3) thing; also (4) at environment. This study examines the elements of supernatural which contained in Minangkabau folktales entitled kaba Cindur Mata title. ThisÂ research technique is data collection, validation of data and analyzing the data. This type of research is descriptive qualitative method. Descriptive method is used to describe the data existing currency figure inÂ Cindur Mata translation story A. Dt. Madjoindo like the element supernatural found in the human, animal, of object and natural environment. The study describes the results of discusses the supernatural element of the story Cindur Mata as follows. Extra ordinary human (magic) contained in the story Cindur Mata on character named Cindur Mata, Dang Tuanku, Tiang Bungkuk. Animals that have district are horse (Gumarang), buffalo (Binuang), and chicken (Kinantan). Magical objects are rare and may lead to the impression gained is keris bungkuk, percussion prohibition, amulet, boat and fire mirror (suryakanta). Natural environment or natural state generally has a large influence on the story Cindur Mata is single lightening and thunder.